2021
DOI: 10.1080/14686996.2020.1812364
|View full text |Cite
|
Sign up to set email alerts
|

Heusler alloys for spintronic devices: review on recent development and future perspectives

Abstract: Heusler alloys are theoretically predicted to become half-metals at room temperature (RT). The advantages of using these alloys are good lattice matching with major substrates, high Curie temperature above RT and intermetallic controllability for spin density of states at the Fermi energy level. The alloys are categorised into half- and full-Heusler alloys depending upon the crystalline structures, each being discussed both experimentally and theoretically. Fundamental properties of ferromagnetic Heusler alloy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
111
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 255 publications
(112 citation statements)
references
References 380 publications
(650 reference statements)
1
111
0
Order By: Relevance
“…In W, there is an almost twofold increase in the crystallite size from 5.4 nm ± 0.2 nm to 9.2 nm ± 0.1 nm associated with the increased crystallinity. CFAS without heating shows noncrystalline or nanocrystalline nature as expected [3]. In the samples grown at 62 • C, on the other hand, a crystallite size of 7.9 nm ± 0.1 nm is obtained.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…In W, there is an almost twofold increase in the crystallite size from 5.4 nm ± 0.2 nm to 9.2 nm ± 0.1 nm associated with the increased crystallinity. CFAS without heating shows noncrystalline or nanocrystalline nature as expected [3]. In the samples grown at 62 • C, on the other hand, a crystallite size of 7.9 nm ± 0.1 nm is obtained.…”
Section: Resultssupporting
confidence: 71%
“…H EUSLER alloys have been investigated intensively due to their half-metallicity at room temperature, which is considered an ideal spin source for spintronic devices [1]- [3]. The alloys can also exhibit other magnetism by controlling the number of valence band electrons in the alloys and the associated magnetic interactions, achieving antiferromagnetism [4], ferrimagnetism [5], topological insulator [6], and spin gapless semiconductor [7].…”
Section: Introductionmentioning
confidence: 99%
“…In 1983, de Groot and his coworkers (de Groot et al, 1983(de Groot et al, , 1984 had shown in their revolutionary studies that these materials belong to a novel class half metal, which has been since then investigated rigorously. By this time, some other interesting properties of Heusler compounds have been pointed out by different research groups (Elphick et al, 2021;Yu et al, 2015;Wu et al, 2020).…”
Section: Introductionmentioning
confidence: 92%
“…The (220) peaks were used to quantify the A2 crystalline ordering (atomic mixing between Ni, Mn and Al), i.e., the increase in Q factor represents the increase in A2 ordering, which typically leads to B2 ordering (atomic mixing between Ni and Mn) with a coexisting (200) peak and L2 1 perfect ordering with coexisting (200) and (111) peaks [12].…”
Section: Ni 2 Mnal Filmsmentioning
confidence: 99%